If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12c + -8 + -5c = 27 Reorder the terms: -8 + 12c + -5c = 27 Combine like terms: 12c + -5c = 7c -8 + 7c = 27 Solving -8 + 7c = 27 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + 7c = 27 + 8 Combine like terms: -8 + 8 = 0 0 + 7c = 27 + 8 7c = 27 + 8 Combine like terms: 27 + 8 = 35 7c = 35 Divide each side by '7'. c = 5 Simplifying c = 5
| 8b+4b-b=55 | | 2x-19=12x-53 | | 13+5b-2b=37 | | -50+80= | | 8a+7-5a=31 | | 2n-11=-6+n | | 2(2z-1)-2(5-3z)=2 | | 9c+4c-c=48 | | 6y-4y+y=18 | | 3x-12=2(x-3) | | -50-80=what | | 4a+9a-6a=42 | | -8(n+2)+19=-5n-9 | | 15-2b=-8(2b+2)+3 | | 3l+2=-l-2 | | (4x+5y+-6)*3= | | -18-5x=-(3+8x) | | (12x+15)(12X-15)=144x-225 | | 3ay-6a+7y-14=0 | | (8x+9)(8x-9)=64x-81 | | 4x^3-28x+40x=0 | | 142-5x=22x+19 | | 3-6x=12+3x | | 8m+6(m-8)=50 | | 5=4.9-(-x) | | -33=3-4(k+1) | | 4+7x+1=10 | | 0.5x+3=0.3x-5 | | x^4+-9x^2+2=0 | | 0.4x^2+5.4x+14.8=0 | | (2r+6)(2r-6)= | | (2r+6)(2r-6)= |